2014
DOI: 10.1007/s10551-014-2439-6
|View full text |Cite
|
Sign up to set email alerts
|

Social Entrepreneurship and Business Ethics: Does Social Equal Ethical?

Abstract: This editorial to the special issue addresses the often overlooked question of the ethical nature of social enterprises. The emerging social entrepreneurship literature has previously been dominated by enthusiasts who fail to critique the social enterprise, focusing instead on its distinction from economic entrepreneurship and potential in solving social problems. In this respect, we have found through the work presented herein that the relation between social entrepreneurship and ethics needs to be problemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(139 citation statements)
references
References 27 publications
4
129
0
6
Order By: Relevance
“…Thus far, the corporate responsibility literature has described innovation as either "entrepreneurial action linked with social causes" (social entrepreneurship) or "environmentally focused innovation" (for example, clean technologies) [73,74]. Our results illustrate that responsible innovation cannot be confined to social entrepreneurship or environmental issues only, but offers a broader framework for corporate action in which private innovators and end users work closely together to ensure that the end products are socially desirable.…”
Section: Discussionmentioning
confidence: 73%
“…Thus far, the corporate responsibility literature has described innovation as either "entrepreneurial action linked with social causes" (social entrepreneurship) or "environmentally focused innovation" (for example, clean technologies) [73,74]. Our results illustrate that responsible innovation cannot be confined to social entrepreneurship or environmental issues only, but offers a broader framework for corporate action in which private innovators and end users work closely together to ensure that the end products are socially desirable.…”
Section: Discussionmentioning
confidence: 73%
“…Whilst prior research has positioned SE hybrids (and social entrepreneurship) as a global movement building a 1 3 social economy distinct from the state and private sectors (Nicholls 2006;Pearce 2003), there remains little analysis within SE research to problematise its ethical commitments (Chell et al 2016). As depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, behind this is a substantive 'deep' back with diverse political foundations that are under-theorised in the ield. Despite calls to move beyond deinition (Light 2008;Mair and Marti 2006;Nicholls 2006), we still see beneits from problematising the theorisation of SE through the alternative lens of business ethics (Bull et al 2010;Chell et al 2016;Dacin et al 2010Dacin et al , 2011Dey and Steyaert 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This formation, named intrapreneurship [intra(corporate) + (entre) preneurship] by Pinchot (1985), allows entrepreneurship within the firm; it was observed that the concept of interorganizational entrepreneurship is used in exchange for the intrapreneurship in the literature (Güney, 2008). The small enterprises plan to make a new investment or risk taking has to identify four key differences: Differences in resource mobilisation, the nature of emergent opportunities, differences in mission and management and performance measurement (Chell et al, 2016).…”
Section: Concept and Definition Of Intrapreneurshipmentioning
confidence: 99%